2023
DOI: 10.1175/mwr-d-22-0337.1
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale Factors Contributing to the Extreme Rainstorm on 20 July 2021 in Zhengzhou, China, as Revealed by Rapid Update 4DVar Analysis

Abstract: The purpose of this study is to diagnose mesoscale factors responsible for the formation and development of an extreme rainstorm that occurred on 20 July 2021 in Zhengzhou, China. The rainstorm produced 201.9 mm rainfall in one hour, breaking the record of mainland China for 1-h rainfall accumulation in the past 73 years. Using 2-km continuously cycled analyses with 6-min updates that were produced by assimilating observations from radar and dense surface networks with a four-dimensional variational (4DVar) da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…(2022) using Weather Research & Forecasting (WRF)‐ARW model simulations reproduced the major synopticscale weather systems and proposed that the arc‐shaped updrafts transporting rain water into the same trailing region were the main dynamical driver for the 201.9 mm hourly rainfall. The presence of an arc‐shaped convergence zone was also found in another independent simulation study (Wei et al., 2022) and in analyses with real‐time radar data assimilation (Sun, Li, et al., 2023). In spite of the consensus on the presence of arc‐shaped updrafts, the modeling studies above employed one‐moment schemes in which the variations of raindrop size distributions, which were characterized by rather high temporal‐spatial variability in this event (Cui et al., 2024) and directly linked to surface rainfall accumulations (Huang et al., 2020; H. Li et al., 2023), was overlooked, suggesting a need to examine the interactions between the storm‐scale kinematics and microphysics.…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…(2022) using Weather Research & Forecasting (WRF)‐ARW model simulations reproduced the major synopticscale weather systems and proposed that the arc‐shaped updrafts transporting rain water into the same trailing region were the main dynamical driver for the 201.9 mm hourly rainfall. The presence of an arc‐shaped convergence zone was also found in another independent simulation study (Wei et al., 2022) and in analyses with real‐time radar data assimilation (Sun, Li, et al., 2023). In spite of the consensus on the presence of arc‐shaped updrafts, the modeling studies above employed one‐moment schemes in which the variations of raindrop size distributions, which were characterized by rather high temporal‐spatial variability in this event (Cui et al., 2024) and directly linked to surface rainfall accumulations (Huang et al., 2020; H. Li et al., 2023), was overlooked, suggesting a need to examine the interactions between the storm‐scale kinematics and microphysics.…”
Section: Introductionsupporting
confidence: 66%
“…(2022) employed the similar rational to quantify the size sorting signatures in convections. These approaches assume the presence of a single inflow, and there is a lack of study addressing the case of multiple directions of size sorting in presence of multi‐directional inflows (Sun, Li, et al., 2023; Wei et al., 2022; Yin et al., 2022). Here, we present a seminal approach to quantify the size sorting directions based on coupled Z DR ‐ K DP separation signatures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the convection-permitting simulation, Hua et al (2020) found that the orographic gravity waves generated by the small-scale Taiyue Mountain cause adiabatic cooling and saturation of the lower troposphere, which is conducive to the subsequent convection initiation. Sun et al (2023) illustrated that the development of barrier airflow and downslope airflow in the vicinity of the Taihang Mountains is key to the intensification of rainstorm. Observations from the Mesoscale Alpine Programme project revealed that the presence of isolated mountains and valleys, with horizontal scales much smaller than the main Alpine ridge, significantly affects the precipitation patterns over the southern Alpine slope (Medina & Houze, 2003;Rotunno & Ferretti, 2003;Smith et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al. (2023) illustrated that the development of barrier airflow and downslope airflow in the vicinity of the Taihang Mountains is key to the intensification of rainstorm. Observations from the Mesoscale Alpine Programme project revealed that the presence of isolated mountains and valleys, with horizontal scales much smaller than the main Alpine ridge, significantly affects the precipitation patterns over the southern Alpine slope (Medina & Houze, 2003; Rotunno & Ferretti, 2003; Smith et al., 2003).…”
Section: Introductionmentioning
confidence: 99%